AB0523 An analysis of the factors influencing the body image disturbance with systemic lupus erythematosus living in china. (15th June 2017) - Zhao, Q; Cui, Y; Li, L; Chen, S; Zhou, C; Gu, Z
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic, autoimmune rheumatic disease that can affect multiple systems/organs in the body and is characterized by relapses and remission, usually affects women in the reproductive age group. SLE may cause inflammation activity and damage in any of the organs, often resulting in decreased physical, emotional and social abilities, depression, pain, fatigue, visible or invisible changes in appearance. Recent studies have indicated that body image disturbance (BID) can lead to a variety of cognitive, emotional and behavioral changes. BID will cause the individual having a negative perception of the body, negative emotional experience and the corresponding behavior disorders. Objectives: To explore the relationship between social and economic status, disease activity, mental state, self-esteem, quality of life and the essential BID with Systemic Lupus Erythematosus Living in China. Methods: The investigation is from in October 2015 to December 2016 at the Affiliated Hospital of Nantong University. There are 109 cases of hospitalized patients, including 8 cases of male, female 101 cases, mean age is 35.3±12.2. Scale including body image disorder scale (BID), respectively. Body image was assessed using the Body Image Disturbance Questionnaire (BIDQ) which contains seven scaled items scored from 0 (not affected) to 8 (extremely affected) pertaining to appearance-related concerns (BIDQ1); mental preoccupation (BIDQ2); emotional distress (BIDQ3); social, occupational, or functional impairment (BIDQ4); social life interference (BIDQ5) and educational, occupational, or other functional interferences (BIDQ6); and behavioural avoidance (BIDQ7). Systemic lupus erythematosus disease activity index (SLEDAI); the hospital anxiety and Depression Scale (HADS) in systemic lupus erythematosus; disease-specific HRQOL measure for adults with SLE (Lupus QOL), including health (PH), pain (PN), planning (PL), intimate relationship (IR), a burden to others (BV), emotional Health (EH), body image (BI), fatigue (F). Spearman's coefficient for nonparametric and Pearson's coefficient for parametric data were computed. Variables that were significant in univariate analysis were included in a multivariate linear regression model. All p-values less than 0.05 were considered statistically significant. Results: SLE patients were most concerned about their body size (33.38%) and skin (32.23%), 55.34% SLE patients were more concerned about the change of body shape caused by disease. There was significant correlation between BID and disease status, psychological status and quality of life in patients with SLE. Physical health is correlated with BD1, Pain is correlated with BID1, BID4–7, Planning is correlated with BID2, BID4–7, Intimate relationships is correlated with BID4–7, Burden to others is correlated with BID3–7, Emotional health, fatigue are associated with BID3–7. Anxiety and depression also affect BID, anxiety is an important predictor of BIDQ1, BIDQ3–6, depression is a predictor of BIDQ2, BIDQ 3–6. Conclusions: Patients with Systemic Lupus Erythematosus Living in China are much easier bear with BID, anxiety, depression, less quality of life will lead to BID, in view of the body image perspective, this study will help explore the influence factors of BID in patients with SLE. Acknowledgements: The study was supported by The Natural Science Foundation of China (81401124). Disclosure of Interest: None declared